PENGARUH KONTEN TIKTOK NADYA KHIETNA PUTRI (@MIEAYAMTHEBSTT) TERHADAP TINGKAT KETIDAKPERCAYAAN DIRI (INSECURE) REMAJA DI KOTA BATAM - Siregar, Dolly Martend; Abidin, Sholihul (SCIENTIA JOURNAL, 2023)
One of the social media that is great demand by the people of Indonesia is TikTok. TikTokis a social media that is used to create content in the form of short videos. On TikToksomeone can become famous because of their content, these people are called tiktokers.One of the Tiktokers with interesting content is Nadya Khietna Putri, whose content has adistinctive feature that is, she makes TikTok videos of lypsinc and dance by displaying cuteand adorable facial expressions. Because she has an adorable face, many TikTok users areinterested in the content she’s uploads. But behind the many TikTok users who like Nadya'scontent there are also several other users who feel insecure about her beauty, they feel thatthey are not beautiful as Nadya and they often compare themselves with Nadya. They mostlyyoung women, felt that they could not be like Nadya, who was often praised and the centerof attention. It is because of this phenomenon that researchers want to examine whetherthere is an influence from Nadya Khietna Putri's TikTok content on the level of insecurity ofadolescents in Batam City. The theory used is S-O-R theory which assumes that the mediacan have an immediate and direct impact on audiences. This study uses a quantitativeresearch design with associative analysis. Data processing in this study used IBM SPSS 25software. The results showed that the t value for the variable Nadya Khietna Putri's TikTokContent (X) was 5.809 for the level of insecurity (Y) with a significance value of 0.000. Thisshows that t count is 5.809 > t table is 1.984 with a significance of 0.05, so it can beconcluded that H0 is rejected and Ha is accepted